Metode Tahfidz Al-Qur’an Secara Mandiri: Studi Kasus Pondok Pesantren Darussalam Parmeraan Kecamatan Dolok Kabupaten Padang Lawas Utara - Umaruddin Ritonga (UIN SYEKH ALI HASAN AHMAD ADDARY PADANGSIDIMPUAN, 2021)
This study aims to describe the implementation of tahfidz Al-Qur'an in Darussalam Parmeraan Islamic Boarding School, Dolok District, North Padang Lawas Regency. The results showed that the method of tahfidz Al-Qur'an independently applied by students at the Islamic Boarding School Darussalam Parmeraan, Dolok District, North Padang Lawas Regency was the Wahdah Method, the Kitabah Method, the Sima'i Method, and the Jama'i Method.Meanwhile, the motivation of tahfidz Al-Qur'an independently for students is to be able to become prayer priests, make parents proud with their memorization, and know Islamic teachings correctly. In addition, there is extrinsic motivation, namely the influence of teachers who can teach well, parents who tell them to study hard and the influence of their friends who get high marks or are good at the Koran